Online channel sales premia in times of COVID-19: First evidence from Germany - Joachim Wagner (Economies, 2023)
A presence on the web tends to be important for firms. Empirical studies show that firms with a better performance across various dimensions, and firms that are more internationally active, tend to have a website. Furthermore, a website helped firms to survive during the COVID-19 pandemic. An open question that is not discussed in the literature is how the use of online channels for sales is related to various dimensions of firm performance. This study contributes to the literature by using a unique recently released set of firm level data from Germany to investigate for the first time the links between online channels sales and firm characteristics. In a robustness check, the empirical investigation was replicated using strictly comparable firm level data from nine European countries, namely Austria, Belgium, Denmark, Finland, France, Ireland, Luxembourg, the Netherlands, and Sweden.
Keywords: D22; L25; 330; COVID-19; firm performance; Germany 2021 Enterprise Survey Data Set; online channels sales